OSS (ONLINE SINGLE SUBMISSION) PROGRAM INNOVATION TO SUPPORT BUSINESS LICENSE SERVICES AT DPMPTSP SIDOARJO REGENCY - Ayu Wulandari, Herdine; Sukmana, Hendra (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective:  the purpose of this study is to analyze and describe the Innovation of the Online Single Submission (OSS) Program in improving business licensing services at the Investment and One-Stop Integrated Services Office (DPMPTSP) of Sidoarjo Regency using the innovation diffusion theory from Everett Rogers. The focus of the research is directed at five key indicators of innovation: relative profitability, suitability, complexity, triability, and ease of observability. Method: The method used is a descriptive qualitative approach with purposive sampling techniques on relevant informants. Data were collected through interviews, observations, and documentation, and analyzed with the Miles and Huberman model through the stages of reduction, data presentation, and conclusion drawn. Result: The results of the study show that the Relative Advantage indicatorprovides great benefits such as time efficiency, legal certainty, easy access, and supports the principle of good governance. OSS conformity supports bureaucratic reform and technology-based governance and supports local economic growth. Complexity regarding the difficulty of understanding the terms KBLI and NIB, especially the MSME community. Possible to try OSS allows for initial testing before full launch to help users and governments, OSS Ease of Observability is easy to observe such as improved time efficiency, transparency, and easier access. Novelty: The novelty of this study lies in the comprehensive theory-based evaluation approach of Rogers (1962) to the implementation of OSS in the context of local licensing, which has not been explored in depth. This study confirms that the successful adoption of digital innovations in public services is highly dependent on a combination of system readiness, people's digital literacy, and active support from the government.